التسامح والتعايش في الشعر الجاهلي /Tolerance and Coexistence in Pre-Islamic Poetry - Fawzia Saad Mohammed Al-Qarni, (مجلة الدراسات اللغوية والأدبية (Journal of Linguistic and Literary Studies), 2023)
ملخص البَحث: سعت هذه الدراسة إلى الكشف عن تواجد ظاهرة التسامح الديني، والعيش المشترك بأمن وسلام بين شعوب وشعراء قبائل الجزيرة العربية قديماً قبل مجيء الإسلام، كما هدفت إلى التركيز على صفات المتسامح فمن خلال صفات الفرد المتسامح يمكننا النفاذ إلى محور دراساتنا التسامح والعيش المشترك في ربوع جزيرة العرب. ولمعالجة إشكالية البحث فقد اعتمدت الباحثة على المنهج الوصفيّ التحليليّ المتسم بالاستقصاء والتتبع والتحليل. وجاء في خاتمة البحث ما أثبته الشعْر الجاهلي عند طائفة من الشعراء، من قدرة تقبل شعوب الجزيرة للآخرين وفسح مجال العيش معهم، وأن الحكمة تمثل فلسفة الشاعر في الحياة، وتصدر بعفوية مرتبطة بحالة الشاعر النفسية والقيم التي تربى عليها. الكلمات المفتاحية: التسامح، التعايش، القيم والحكم، شعراء الجاهلية. Abstract: This study sought to reveal the presence of the phenomenon of religious tolerance and coexistence in security and peace among the peoples and poets of the tribes of the Arabian Peninsula in the past, before the advent of Islam. It also aimed to focus on the qualities of the tolerant. Through the characteristics of the tolerant individual, we may access the focus of our studies: (tolerance and coexistence) throughout the Arabian Peninsula. To address the research problem, the researcher relied on the descriptive analytical approach, which is characterized by investigation, tracking and analysis. At the end of the research it is proven through the pre-Islamic poetry by a group of poets, that the peoples of the Arabic peninsular accepted others and made room for living with them. The study also proved that wisdom represents the poet's philosophy in life, and it is conveyed with spontaneity associated with the poet's psychological condition and the values on which he was raised. Keywords: tolerance, coexistence, values and governance, Pre-Islamic poets. Abstrak: Kajian ini membahasakan wujudnya amalan toleransi beragama dan hidup bersama dalam suasana aman dan tenteram di kalangan masyarakat dan penyair suku-suku semenanjung Arab suatu ketika dahulu, iaitu sebelum kedatangan Islam. Ia juga bertujuan untuk memfokuskan kepada ciri-ciri toleransi yang ada pada individu yang mengamalkan toleransi. Melalui ciri-ciri ini, kita boleh mengenali fokus kajian ini: (toleransi dan hidup bersama) di seluruh Semenanjung Tanah Arab. Bagi menjawab permasalahan kajian, pengkaji menggunakan pendekatan analisis deskriptif, yang bercirikan peninjauan, penelitian dan analisis. Kajian terhadap puisi Arab Jahili menyimpulkan bahawa masyarakat semenanjung Arab mampu menerima orang lain dan memberi ruang untuk hidup bersama mereka. Kajian juga mendapati bahawa kata-kata hikmah adalah cerminan falsafah penyair tentang kehidupan, dan ianya lahir secara spontan dan berkait rapat dengan kondisi psikologi penyair dan nilai-nilai yang menjadi tunjang asuhan mereka sejak kecil. Kata kunci: toleransi, kewujudan bersama, nilai dan pemerintahan, penyair pra-Islam.